Subcutaneous Immunotherapy Improves the Symptomatology of Allergic Rhinitis - Edmir Américo Lourenço; Eduardo José Caldeira; César Alexandre Fabrega Carvalho; Marcelo Rodriques Cunha; Marcus Vinícius Henriques Carvalho; Saulo Duarte Passos (International Archives of Otorhinolaryngology, 2016)
Abstract